Improved detection of nasopharyngeal cocolonization by multiple pneumococcal serotypes by use of latex agglutination or molecular serotyping by microarray. - Turner, P; Hinds, J; Turner, C; Jankhot, A; Gould, K; Bentley, S; Nosten, F; Goldblatt, D (2011)
Identification of Streptococcus pneumoniae in the nasopharynx is critical for an understanding of transmission, estimates of vaccine efficacy, and possible replacement disease. Conventional nasopharyngeal swab (NPS) culture and serotyping (the WHO protocol) is likely to underestimate multiple-serotype carriage. We compared the WHO protocol with methods aimed at improving cocolonization detection. One hundred twenty-five NPSs from an infant pneumococcal-carriage study, containing ≥ 1 serotype by WHO culture, were recultured in duplicate. A sweep of colonies from one plate culture was serotyped by latex agglutination. DNA extracted from the second plate was analyzed by S. pneumoniae molecular-serotyping microarray. Multiple serotypes were detected in 11.2% of the swabs by WHO culture, 43.2% by sweep serotyping, and 48.8% by microarray. Sweep and microarray were more likely to detect multiple serotypes than WHO culture (P < 0.0001). Cocolonization detection rates were similar between microarray and sweep, but the microarray identified the greatest number of serotypes. A common serogroup type was identified in 95.2% of swabs by all methods. WHO methodology significantly underestimates multiple-serotype carriage compared to these alternate methods. Sweep serotyping is cost-effective and field deployable but may fail to detect serotypes at low abundance, whereas microarray serotyping is more costly and technology dependent but may detect these additional minor carried serotypes.